MACAW a media access protocol for wireless LAN's. - Bharghavan, Vaduvur (Computer communication review.)
In recent years, a wide variety of mobile computing devices has emerged, including portables, palmtops, and personal digital assistants. Providing adequate network connectivity for these devices will require a new generation of wireless LAN technology. In this paper we study media access protocols for a single channel wireless LAN being developed at Xerox Corporation's Palo Alto Research Center. We start with the MACA media access protocol first proposed by Karn [9] and later refined by Biba [3] which uses an RTS-CTS-DATA packet exchange and binary exponential back-off. Using packet-level simulations, we examine various performance and design issues in such protocols. Our analysis leads to a new protocol, MACAW, which uses an RTS-CTS-DS-DATA-ACK message exchange and includes a significantly different backoff algorithm.